From Street to Cyberspace: Digital Transformation for Community-Oriented Policing - Muchtar, Jarot (Indonesian National Police Academy, 2025)
This study quantitatively evaluates the impact of digital transformation on community-oriented policing (COP) in Semarang, Indonesia, focusing on accessibility, trust, and collaboration. A survey of 523 community members across four sub-districts (Semarang Tengah, Banyumanik, Tembalang, Gunungpati) was conducted, supplemented by secondary data from Semarang Police reports and Portal Semarang Satu Data. Results showed digital platforms increased accessibility (M = 4.29, SD = 0.60), trust (M = 4.09, SD = 0.67), and collaboration (M = 4.00, SD = 0.77). Multiple regression identified digital literacy (β = 0.121, p = 0.001) and platform usability (β = 0.112, p = 0.017) as significant predictors of trust (R2 = 0.045). ANOVA revealed sub-district differences in accessibility (F(3, 519) = 36.55, p < 0.001). Rural areas lagged in digital literacy (48.2% vs. 88.2% urban). The study